Change in pulmonary arterial compliance and pulmonary pulsatile stress after balloon pulmonary angioplasty - KOCAKAYA, DERYA; YILDIZELİ, BEDRETTİN (My University, 2022)
Objective: Although the underlying pathology of chronic thromboembolic pulmonary hypertension (CTEPH) is mechanical obliteration of the major pulmonary vessels, high pulsatile stress penetrating into the normal distal pulmonary microvasculature resulting from reduced pulmonary arterial compliance (CPA) may cause progressive deterioration in pulmonary hemodynamics. Hypothetically, balloon pulmonary angioplasty (BPA) may be beneficial in reducing CPA and pulsatile stress in patients with CTEPH. Methods: In total, 26 patients with available pre- and post-BPA right heart catheterization results were included in the study. BPA was performed in a series of staged procedures by 2 experienced interventional cardiologists. Results: The median CPA showed a 59.2% increase (1.03 to 1.64 mL/mm Hg, p=0.005). The median pre-BPA pulsatile stress product decreased by 20.7% (4,266 to 3,380 mm Hg/min, p=0.003). A linear regression model established that the percent change in CPA after BPA accounted for 21.8% of the explained variability in the change in 6-minute walk test (p=0.009). Conclusion: Our results indicate that BPA decreases CPA and pulmonary pulsatile stress. These changes may be partly responsible for the improvement in functional capacity after BPA.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); balloon angioplasty; compliance; pulmonary embolism; pulmonary hypertension; pulsatile flow; HYPERTENSION; STIFFNESS; MORTALITY; balloon angioplasty; compliance; pulmonary embolism; pulmonary hypertension; pulsatile flow